The Effects of Width on the Strength of Adhesively Bonded Z Joints Subjected to Tensile Loads - Adin, Hamit; Turgut, Aydin (Taylor & Francis Ltd, 2013)
In this study, the effect of the adherend width on the tensile strength and the failure load of Z joints was analyzed both experimentally and numerically using two adhesives with different properties. Atlac (TM) 580 and Flexsotix (TM) were used as adhesives, and adherends were prepared with two different composite materials. To identify the mechanical properties of the adhesives, the bulk specimen method was used. Then, the Z joints were prepared using the aforementioned adhesives. The Z joints were subjected to tensile loads in the experiments. The stress analyses were performed using a three-dimensional finite element method (3D FEM). The 3D FEM analyses were performed with ANSYS (10.0). The 3D FEM analyses were performed to investigate the stress distributions in the adhesive layers in the Z joints. The numerical results compared favorably with the experimental results, and were found to be quite reasonable. The results showed that the joint strength increased when the specimen width (b) was increased. To maximize the performance of the joint for either adhesive, b = 15 mm was found to be the most suitable value for the width.
Keywords: Adhesive; ANSYS; Finite element method (FEM); Stress analysis; Z joints